2014
DOI: 10.1007/s10911-013-9313-5
|View full text |Cite
|
Sign up to set email alerts
|

Colostrogenesis: IgG1 Transcytosis Mechanisms

Abstract: Biological transport of intact proteins across epithelial cells has been documented for many absorptive and secretory tissues. Immunoglobulins were some of the earliest studied proteins in this category. The transcellular transport (transcytosis) of immunoglobulins in neonatal health and development has been recognized; the process is especially significant with ungulates because they do not transcytose immunoglobulins across the placenta to the neonate. Rather, they depend upon mammary secretion of colostrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
70
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 123 publications
0
70
0
6
Order By: Relevance
“…Maternal iodine supplementation altered the expression of B2M, PIGR and MYC in the neonatal lamb. Previous physiological studies have associated these genes with intestinal immunoglobulin (Ig) transfer (Bruno et al, 2004;Baumrucker and Bruckmaier, 2014). It is evident also that THRB expression at the newborn intestinal level is diminished following maternal prepartum supplementation (CaIO 3 ) in conjunction with reduced free T 3 concentrations in these animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal iodine supplementation altered the expression of B2M, PIGR and MYC in the neonatal lamb. Previous physiological studies have associated these genes with intestinal immunoglobulin (Ig) transfer (Bruno et al, 2004;Baumrucker and Bruckmaier, 2014). It is evident also that THRB expression at the newborn intestinal level is diminished following maternal prepartum supplementation (CaIO 3 ) in conjunction with reduced free T 3 concentrations in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…At birth, the ruminant intestinal tract is undergoing a maturational process in preparation for colostrum ingestion and absorption before gut closure. Due to the requirement for B2M in the maturation and functioning of FcRn (Baumrucker and Bruckmaier, 2014) and the increased relative expression of B2M in the ileum of CaIO 3 lambs at 1 h postpartum it was concluded that iodine supplementation of the dam has no negative influence on the functioning of the FcRn receptor. Additionally, the lower expression of PIGR and increased serum IgG in non-supplemented progeny is in agreement with Johansen et al (1999) who found that PIGR knockout mice had increased levels of serum IgG in comparison to PIGR abundant mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is an expensive and time-consuming test, requiring an incubation period of 18-24 h. In contrast, ELISA method has a higher throughput, is less costly and analysis can be completed in a much shorter time (Lee et al 2008). Consequently, recent research has used ELISA method to quantify IgG levels in colostrum, plasma and sera (Vetter et al 2013;Baumrucker and Bruckmaier 2014;Gelsinger, Smith, et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mammary secretions change dramatically from colostrum (‘first milk’) to mature, main-phase milk during the immediate post-partum period. Broadly, colostrum tends to be more protein-rich and lipid-poor than later milk, and is particularly rich in immunoglobulins and innate anti-microbial factors1234567. The change to mature milk represents a switch to more energy-rich nutrition in which sugars and fats may predominate12.…”
mentioning
confidence: 99%
“…At the other extreme are species with haemochorial placentae (e.g. humans) whose placentae transport immunoglobulins from maternal to foetal blood circulations prior to birth, although this is confined to immunoglobulin G (IgG)234.…”
mentioning
confidence: 99%